Biologia floral de Zeyheria tuberculosa (Bignoniaceae) - Souza, Camila Vaz de [UNESP] (2015)
The Bignoniaceae family is a good model for studies about evolutionary diversification that gave rise to the diversity of tropical plant communities, and the interaction with pollinators is a determining factor. Zeyheria tuberculosa is an endangered species and has characteristics related to melittophily syndrome. Information on the reproduction of this species may help to understand the ecological processes that may have led this species to be included in the Red List of endangered species. This goal of this study was to investigate the floral biology of Z. tuberculosa, focusing on the pattern of nectar secretion and the functional and structural characteristics of the floral nectary, which is the responsible for producing the essential resource for maintaining the interaction with pollinators. The results were divided into two sections that deal with specific and complementary issues. The first includes information about the events of floral anthesis, the pollination ecology and the pattern of nectar secretion in plants of Z. tuberculosa located in semi-deciduous forest fragments, immersed in a modified landscape. The second deals with the structure and functioning of the floral nectary of this species, focusing on the characteristics related to the type of secretion. For Chapter 1, we monitored flowers throughout anthesis; we performed focal observations of floral visitors and captured them to examine the pollen deposition area; recorded the percentage of viable pollen grains and the period of stigma receptivity; obtained data on the morphometry of flowers and pollinator bees; made self-incompatibility tests to assess the dependence of pollen vectors for cross-fertilization; evaluated the dynamics of nectar secretion through the volume, concentration and total milligrams of sugars parameters, using the latter parameter to calculate the caloric supply available to pollinators by flower and plant, and we carried out analyzes on the ...